Strategy development of tofu agroindustry (Case of Pak Lutfi's Tofu) - Putri, Dini Amalia; Dewi, Ilma Satriana (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The tofu agroindustry is a product made from soybeans which is widely cultivated, especially in Pandau Jaya village, Siak Hulu District, Kampar Regency. One of the tofu industries that has been operating for quite a long time in the area is the